(untitled) (Global Journal of Management and Business Research, 2016)
The incompatibility of articles 42 and 63 of the treaty relating to the Organization for the Harmonization of Business Law in Africa (OHADA treaty) and article 1 (3) of the constitution of Cameroon gives rise to the question: is the OHADA treaty constitutionally valid in Cameroon given its mixed legal system? The author answers in the affirmative. The paper seeks to investigate into the constitutional validity of the OHADA treaty. In so doing, the paper shall explore the Cameroonian legal system and some key provisions of the OHADA Treaty, which will be highly selective for this article with the view to determine whether the Treaty establishing OHADA is constitutionally valid in Cameroon. The value of this article lies in the insight it offers into OHADA and Cameroon#x2019;s legal system.